Bioactivities of Ketones Terpenes: Antifungal Effect on F. verticillioides and Repellents to Control Insect Fungal Vector, S. zeamais - Pizzolitto, Romina Paola (2015)
Maize is one the most important staple foods in the world. However, numerous pests, such as fungal pathogens, e.g., Fusarium verticillioides, and insects, such as Sitophlilus zeamais, attack maize grains during storage. Many F. verticillioides strains produce fumonisins, one of the most important mycotoxin that causes toxic effects on human and animal health. This situation is aggravated by the insect fungal vector, Sitophlilus zeamais, which contributes to the dispersal of fungal spores, and through feeding damage, provide entry points for fungal infections. The aim of this study was to evaluate in vitro bioassays, the antifungal activity on F. verticillioides M3125 and repellent effects against S. zeamais of ketone terpenes. In addition, we performed Quantitative structure?activity relationship (Q-SAR) studies between physico-chemical properties of ketone terpenes and the antifungal effect. Thymoquinone was the most active compound against F. verticillioides (Minimum Inhibitory Concentration, MIC: 0.87) affecting the lag phase and the growth rate showing a total inhibition of growth at concentration higher than 2 mM (p < 0.05). The Q-SAR model revealed that the antifungal activity of ketone compounds is related to the electronic descriptor, Pi energy. Thymoquinone showed a strong repellent effect (−77.8 ± 8.5, p < 0.001) against S. zeamais. These findings make an important contribution to the search for new compounds to control two stored pests of maize.